The Correlation between Blood Flow Rate with Arteriovenous Fistula Thrombosis in Patients with End-Stage Renal Disease at Dr. Zainoel Abidin General Hospital in Banda Aceh - Shafira, Chikita Adinda Raudhatun; Habibie, Yopie Afriandi; Alia, Dina (Journal of International Surgery and Clinical Medicine, 2025)
Introduction: Thrombosis is a complication that may arise in End-Stage Renal Disease (ESRD) patients with an arteriovenous fistula (AVF), usually caused by stenosis (narrowing of the vein more than 50% of its diameter) and changes in blood flow rate (BFR). The aim of this study is to explore the relationship between blood flow rate and the incidence of AVF thrombosis in patients with ESRD at Dr. Zainoel Abidin General Hospital Banda Aceh. Methods: In this study, a cross-sectional design was employed to investigate ESRD patients who had undergone the AVF procedure at Dr. Zainoel Abidin General Hospital Banda Aceh from October to November 2023. The study examined Blood Flow Rate values obtained via Doppler ultrasound. The data were analyzed using SPSS version 26 and the contingency coefficient (Cramer's V) to assess the relationship between the variables. Result: 51 patients were sampled. The average BFR value six weeks after surgery in the event of thrombosis and non-thrombosis was 274 ml/min and 786,8 ml/min. There was a significant correlation between BFR values with the incidence of AVF thrombosis (p = 0.000 and Cramer’s V = 0,658) Conclusion: Inadequate blood flow through the fistula may contribute to clot formation, leading to fistula failure in patients undergoing hemodialysis. Optimizing monitoring and early intervention for blood flow in AVF may help reduce the incidence of thrombosis and improve patient outcomes.